(3JdHjS EHdjSs - (3Hf GdLhRj, LeGd GdOjf CHj GdaQLs ((3GdbGgQIs (3OGQ GdaLQ ddJQGKs, 2004)
(3jJfGhd gPG GdcJGH GdBKGQ GdhGQOI HCf Gddg eY jO GdLeGYI hcPdc Pe GdHOY hGdeHJOYjfhGdJMPjQ ef aJf EHdjS hecGFOgs
hurg
5
Keywords: (3GdLfs; (3GdTjGWjfs